Pemanfaatan Internet Of Things (IOT) Oleh Pemustaka Dalam Pencarian Informasi Di Dinas Kearsipan dan Perpustakaan Provinsi Sumatera Barat - Latipul Basri Hutabarat (Bridge : Jurnal Publikasi Sistem Informasi dan Telekomunikasi, 2024)
The purpose of this research is (1) to determine the use of the Internet of Tings (IoT) to help simplify the process of searching for information at the Archives and Library Service of West Sumatra Province, (2) to determine the implementation of the Internet of Tings (IoT) in searching for information in libraries can increase the effectiveness and efficiency of services at the West Sumatra Province Archives and Library Service, (3) to find out what Internet of Things (IoT) devices can be used to assist the information search process at the West Sumatra Province Archives and Library Service. Measurement of the Internet of Things (IoT) is seen through four indicators, namely OPAC, RFID, information literacy and recommendation services. Measuring search information is seen through five indicators, namely, cognitive needs, affective needs, personal integration needs, social integration needs and fantasy needs. This research is quantitative research with descriptive methods. The population in this study was all users at the West Sumatra Province Archives and Library Service, using a random sampling technique. The main instrument used is a research questionnaire whose validity and reliability have been tested with a sample size of 100 respondents. The research results are: (1) The Internet of Things (IoT) variable has a total average score of 3.46. This indicates that the score is on an interval scale of 3.26-4.00, which means it is classified as very good. (2) The information search variable has a total average score of 3.23. This indicates that the score is on an interval scale of 2.51-3.25, which means it is in the good category. (3) The influence of the Internet of Things (IoT) on information searches at the West Sumatra Province Archives and Library Service. In the hypothesis test, the result was 0.398, which means that information needs have a significant relationship with the use of collections at the Sawahlunto City Library and Archives Service, as well as in the table model summary obtained R = 0.288. Then R2 = 0.083. If converted into a percentage, it is 28.8%, this shows that the influence of the Internet of Things (IoT) on information search is 28.8% and the remaining 71.2% is influenced by other factors. Overall, the results of the research analysis can be concluded by researchers that there is a significant influence on the Internet of Things (IoT) on information searches at the West Sumatra Province Archives and Library Service.